Sondagem de relações entre variáveis paternas, problemas de comportamento e desempenho acadêmico de pré-escolares - Fantinato, Aline Costa (Universidade Federal de São Carlos, 2016)
The role that the father plays in the family context is in the process of transformation, becoming a figure of greater affective involvement with the children. The father as well as the mother are important figures for the child, but there are few studies that investigate the father under his own eyes. Thus, the present study aimed to: (a) compare educational social skills, the characteristics of the marital relationship, the abuse potential for child maltreatment, according to the father's opinion, among the parents groups of preschool children who Present behavioral problems, low academic performance or typical development; (B) compare the index of behavioral problems according to the father's opinion among groups of preschoolers with behavioral problems, low academic performance or typical development, and (c) relate the variables. 105 men participated in the study, 45 parents of children with typical development; 29 parents of children with behavioral problems, and 31 parents of children with low academic achievement, and their children's teachers (N = 26). To achieve the goals: (a) parents responded to the Social Skills Inventory, Conjugal Relationship Questionnaire and Abuse Potential Inventory, and (b) teachers and parents answered the Skills and Difficulties Questionnaire (SDQ). The data obtained in the teachers' evaluation for the SDQ and the academic part of the Social Skills Rating System (SSRS) were used to divide the groups. To compare the results of the three groups, we used the t test, considering the comparison of two groups separately and to evaluate the relationships between the variables, the Pearson correlation test was used. The results showed statistically significant differences between the groups, and parents of children with typical development showed a better repertoire of educational social skills, more positive characteristics in the marital relationship and less potential for abuse. The parents of children with behavioral problems and low academic performance seemed to have more difficulties in the marital relationship, as well as in the interaction with the offspring, specifically on the social educational abilities, it was noticed that the parents of children with behavioral problems had the lowest averages. The correlations between the variables showed significant relationships between the adequate behaviors of parents and children; On the other hand, a poor repertoire of educational social skills was related to the behavioral problems of children. There were positive relationships between educational social skills and the positive characteristics of the marital relationship and negative relationships between educational social skills and the potential for paternal abuse. It is concluded that the positive interaction of the father with the offspring constitutes a mechanism of protection to the child development, besides the data of this study point to the influence of the marital relation with the way that the parents interact with the children, emphasizing the importance of the Positive interaction of the father with the children and of a family environment that promotes positive interactions among its members.
Keywords: Educação especial; Pai; Desenvolvimento infantil; Mecanismos de proteção; Fatores de risco; Special education; Father; Child development; Protection mechanisms; Risk factors; CIENCIAS HUMANAS::EDUCACAO